2012
DOI: 10.1016/s1001-0742(11)60771-7
|View full text |Cite
|
Sign up to set email alerts
|

Leaching behavior of enrofloxacin in three different soils and the influence of a surfactant on its mobility

Abstract: The leaching behaviors of enrofloxacin (ENR), a fluoroquinolone group antibiotic, in three different standard soils, namely sandy, loamy sand and sandy loam were investigated according to OECD guideline 312. In addition, the effects of tenside, sodium dodecylbenzenesulfonate (DBS) on the mobility of ENR in two different soils were studied. The mobility of ENR in all three standard soils was very similar and was mostly (98%) concentrated on the top 0-5 cm segment of the soils at pH 5.7. The DBS can enhance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…This is in line with already published studies, which covered the potential of surfactants in general as a potential remediation tool for contaminated soils. 14,15,35,36 The pyrethroid formulation used 1 week before the azadirachtin A product did not show any measurable effects, most probably due to its relatively low surfactant content of <5% Tween.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This is in line with already published studies, which covered the potential of surfactants in general as a potential remediation tool for contaminated soils. 14,15,35,36 The pyrethroid formulation used 1 week before the azadirachtin A product did not show any measurable effects, most probably due to its relatively low surfactant content of <5% Tween.…”
Section: Resultsmentioning
confidence: 93%
“…Surfactants may increase the mobility of SOM-adsorbed lipophilic contaminants, which was already discussed for the direct application of surfactants to soils for remediation purposes or even to support biodegradation . In the field of remediation, DDX and other organic contaminants are mobilized from the soil organic matter which subsequently leads to a depletion. It was also shown that the influence on the mobility of organic pollutants depends on the type of clay minerals in soil. …”
Section: Introductionmentioning
confidence: 99%
“… where m ENR is the spiking weight of ENR for 1m 2 of soil, Δ c ENR is enrofloxacin spiking concentration difference in the soil, ρ is the soil density (1500 kg∙m −3 for silt loam soil) (Zeri et al 2018 ), S soil is the soil area, and h soil is the height of the soil surface Sect. (20 cm due to low mobility of FQs in the soil environment) (Yu et al 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…injection of a hot and pressurized surfactant/water mixture into the main site of contamination, emulsifying the NAPLs and subsequently, the removal of the emulsion by pumps [9][10][11][12][13]. While this is applicable for (expensive) building land as an alternative to removal and extraction, this is not feasible for agricultural soils.…”
Section: Introductionmentioning
confidence: 99%
“…Costs are high and the treatments impair the soil microstructure. In the context of remediation, a mobilization of organic contaminants, such as DDX from soil organic matter is discussed as a first step towards depletion [17,9,[18][19][20][21]12,13,22].…”
Section: Introductionmentioning
confidence: 99%